Current Issues and Challenges in Real Estate Industry: The Way Forward - Wan Zahari Wan Yusoff (Penerbit UTHM, 2022)
Generally, the real estate sector has made a considerable contribution to a nation’s economic growth. The economy of a nation is significantly impacted by favourable changes in the business and real estate markets. Similarly, the decline in the housing market has a big effect on the economy. Therefore, the real estate sector also has to deal with difficult problems that have a big impact on its ability to survive. This book discusses five (5) significant problems that Malaysia’s and the world’s real estate markets are currently confronting. This book also discusses how the country’s real estate sector may be threatened by the issues raised. The book’s approach to offering ideas to meet this difficulty is equally intriguing. Beginning with an overview of the history of the real estate industry, this book goes on to cover the characteristics of the Malaysian real estate market, the origins of the real estate and surveying professions, and various key real estate concepts like cost, value, and market value as well as the highest and best use. This book also demonstrates how technology-based business tycoons have increasingly replaced real estate tycoons as the richest people over the past few decades. This occurs as disruption technology starts to replace conventional business practises throughout industries, including the real estate industry. The effect of COVID-19 on several real estate sectors, including housing, commercial, office, and the hospitality industry, is also covered in length in this book. This book focuses on the key concerns that, whether locally or globally, endanger the real estate business and is written in simple language. Since all activities related to space and buildings, such as commercial activity, daily office activities, teaching and learning activities in institutions of higher learning, and all movements are subject to movement control, the Covid-19 epidemic that has halted all economic activity has also stopped the real estate industry’s consistency against inflation. Due to the constraints imposed by this circumstance, there is now significantly less demand for space in the real estate market. The book also discusses Proptech and technology disruption as threats to the real estate sector. The usage of modern technology has interrupted everyday routines, from using the internet to regular physical practises. This book also covers the economic bubble that developed as a result of overzealous real estate speculation. The topic of property overhang and market mismatch, which continue to be problems in the real estate sector, was also discussed. The discussion also illustrates the effects and outlines potential remedies for the threats mentioned.